(untitled) (Journal of Fatima Jinnah Medical University, 2018)
The silver colloid technique for nucleolar organizer regions (AgNORs) was applied to bone marrow smears in 10 cases of normal morphology marrow and 15 cases of acute myeloblastic leukemia. AgNORs were recorded in the form of ‘clusters’ and ‘dots’ in the myeloblasts. Leukemic blasts contained a significantly lower number of AgNOR ‘clusters’ as compared to normal myeloblasts. The method has the potential of helping in diagnosis of AML and should be adopted while evaluating bone marrow smears.